2002
DOI: 10.1016/s1567-5394(02)00119-6
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric monitoring of laccase-catalysed mediated reactions

Abstract: Six different compounds capable of mediating laccase-catalysed reactions have been tested by cyclic voltammetry. They exhibited quasireversible electrodic behaviour with formal redox potentials ranging from 150 to 800 mV (E 0 Vvs. SCE). The immersion of a laccase-coated glassy carbon electrode (GCE) in mediator solutions generated large cathodic catalytic currents easily recorded by cyclic voltammetry at lowpotential scan rates. This current showed two well-defined pH profiles, which correlated with the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
59
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 27 publications
11
59
0
3
Order By: Relevance
“…40%) current at 0.2 V was obtained at 37°C. These results are in agreement with previous reports where the maximal bioelectrocatalytic activity of Lc from different sources was observed in the temperature range 35 -50°C [41][42][43][44]. While the solubility of O 2 decreases with increasing temperature, the increase in the diffusion coefficient offsets this decrease, resulting in an increased response [37,[45][46] which is in agreement with the results reported for homogeneous ThLc catalysis which has a temperature optimum of 45°C [47].…”
Section: Resultssupporting
confidence: 93%
“…40%) current at 0.2 V was obtained at 37°C. These results are in agreement with previous reports where the maximal bioelectrocatalytic activity of Lc from different sources was observed in the temperature range 35 -50°C [41][42][43][44]. While the solubility of O 2 decreases with increasing temperature, the increase in the diffusion coefficient offsets this decrease, resulting in an increased response [37,[45][46] which is in agreement with the results reported for homogeneous ThLc catalysis which has a temperature optimum of 45°C [47].…”
Section: Resultssupporting
confidence: 93%
“…The appearance of two broad anodic peaks in the reverse scan showed two step oxidation of the AQ reduction product The cathodic peak width (E pc -E pc/2 ) of 34 mV (close to the theoretical value of 30 mV) indicated the transfer of two-electrons as reported by Bard et al [20]. The equal anodic and cathodic currents at pH 9.0, with peak potential difference of 75 mV can be attributed to the almost reversible nature of the overall redox process under these conditions [21]. The variation in voltammetric response indicated the strong dependency of the AQ redox mechanism on the pH of the medium.…”
Section: Resultssupporting
confidence: 82%
“…The two former conditions have been confirmed with acetosyringone, since voltametric and electron paramagnetic resonance studies have shown the true reversibility of the substrate reaction (19) and the long half-life of its phenoxy radical (35). In contrast, the -NO·-radical from HBT inactivates laccase, and due to its high reactivity, decays rapidly to benzotriazole and other inactive compounds (30).…”
Section: Discussionmentioning
confidence: 89%